2016
DOI: 10.1016/bs.mie.2016.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Design of Heteronuclear Metalloenzymes

Abstract: Heteronuclear metalloenzymes catalyze some of the most fundamentally interesting and practically useful reactions in nature. However, the presence of two or more metal ions in close proximity in these enzymes makes them more difficult to prepare and study than homonuclear metalloenzymes. To meet these challenges, heteronuclear metal centers have been designed into small and stable proteins with rigid scaffolds to understand how these heteronuclear centers are constructed and the mechanism of their function. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 135 publications
0
14
0
Order By: Relevance
“…Extensive progress in protein design and engineering enables the construction of artificial metalloenzymes showing efficiency and substrate diversity beyond those of natural systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Heme-containing enzymes active in oxidation chemistry are a fascinating source of inspiration for researchers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive progress in protein design and engineering enables the construction of artificial metalloenzymes showing efficiency and substrate diversity beyond those of natural systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Heme-containing enzymes active in oxidation chemistry are a fascinating source of inspiration for researchers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Turnover number defines the rate at which an enzyme converts its substrate, usually in terms of the number of substrate molecules that can be converted by a single enzyme molecule and can range from a few molecules to several million molecules per second [1].…”
mentioning
confidence: 99%
“…2C). 34 In addition, the rate of O 2 reduction and enzyme turnover number were both positively correlated with heme Eº´ while ROS production remained essentially constant. Rapid stopped-flow kinetics studies found that increased heme Eº´ was associated with increases in the rates of ET, O2 binding, O 2 dissociation, and a slight decrease in O 2 affinity.…”
Section: Metallocofactorsmentioning
confidence: 93%
“…When we replaced the nonheme Fe(II) in Fe B Mb with Cu(I), O 2 reduction activity increased 3-fold. 55 A further study to explain this effect found that the identity of the nonheme metal had minimal impact on heme Eº´, but Eº´ of Cu(II)/Cu(I) is +128 mV higher than nonheme Fe(II)/Fe(III). Since the rate of O 2 reduction is limited by ET, a stronger driving force for ET to bound O 2 is partially responsible for the observed rate enhancement with Cu.…”
Section: Metal Ionsmentioning
confidence: 98%